Teaching professionalism in medical education: A Best Evidence Medical Education (BEME) systematic review. BEME Guide No. 25. (July 2013) - Birden, Hudson; Glass, Nel; Wilson, Ian; Harrison, Michelle; Usherwood, Tim; Nass, Duncan
<x xml:space="preserve">Abstract</x> Introduction: We undertook a systematic review to identify the best evidence for how professionalism in medicine should be taught. Methods: Eligible studies included any articles published between 1999 and 2009 inclusive. We reviewed papers presenting viewpoints and opinions as well as empirical research. We performed a comparative and thematic synthesis on all papers meeting inclusion criteria in order to capture the best available evidence on how to teach professionalism. Results: We identified 217 papers on how to teach professionalism. Of these, we determined 43 to be best evidence. Few studies provided comprehensive evaluation or assessment data demonstrating success. As yet, there has not emerged a unifying theoretical or practical model to integrate the teaching of professionalism into the medical curriculum. Discussion: Evident themes in the literature are that role modelling and personal reflections, ideally guided by faculty, are the important elements in current teaching programmes, and are widely held to be the most effective techniques for developing professionalism. While it is generally held that professionalism should be part of the whole of a medical curriculum, the specifics of sequence, depth, detail, and the nature of how to integrate professionalism with other curriculum elements remain matters of evolving theory.